ANALISIS YURIDIS NOTA KESEPAHAMAN ANTARA KEPOLISIAN NEGARA REPUBLIK INDONESIA DENGAN IKATAN NOTARIS INDONESIA - Puspadewi, Anak Agung Ayu Intan (Jurnal Hukum Saraswati (JHS), 2019)
Memorandum of understanding agreed and signed by the Indonesian Notary Association with the Indonesian National Police Number: 06 / MOU / PPINI / VIII / 2018 Number: B / 46 / VIII / 2018 concerning guidance and law enforcement in an effort to increase professionalism. Agreements made using memorandum of understanding in a legal review have binding or not binding power. Based on the memorandum of understanding agreement that guidance can be carried out by the Indonesian National Police, Regulation the notary position that the Notary Honorary Council has such authority. Based on the above problem, the formulation of the problem used is how to bind the memorandum of understanding signed by the Indonesian National Police with the Indonesian Notary Association and What is the scope of the discussion in the memorandum of understanding signed by the Indonesian National Police with the Indonesian Notary Association. that based on the discussion of the problem, the conclusion is that the strength of the memorandum of understanding by the parties can be binding if in accordance with the legal conditions of the agreement and the parties carry out the agreement. The scope of the memorandum of understanding is in terms of information exchange, coaching, law enforcement and improving the quality of human resources. The intended coaching is to carry out an understanding of notary science.